Managing Thoracic Aortic Aneurysm in Patients with Bicuspid Aortic Valve Based on Aortic Root-Involvement - Norton, Elizabeth; Yang, Bo (Frontiers in Physiology, 2017)
Bicuspid aortic valve (BAV) can be both sporadic and hereditary, is phenotypically variable, and genetically heterogeneous. The clinical presentation of BAV is diverse and commonly associated with a high prevalence of valvular dysfunction producing altered hemodynamics and aortic abnormalities (e.g., aneurysm and dissection). The thoracic aortic aneurysm in BAV frequently involves the proximal aorta, including the aortic root, ascending aorta, and aortic arch, but spares the aorta distal to the aortic arch. While the ascending aortic aneurysm might be affected by both aortopathy and hemodynamics, the aortic root aneurysm is considered to be more of a consequence of aortopathy rather than hemodynamics, especially in younger patients. The management of aortic aneurysm in BAV has been very controversial because the molecular mechanism is unknown. Increasing evidence points toward the BAV root phenotype (aortic root dilation with aortic insufficiency) as having a higher risk of catastrophic aortic complications. We propose more aggressive surgical approaches toward the BAV with root phenotype.